Maori Development: Reflections and Strategic Directions - Durie, Mason (He Pukenga Kōrero: a journal of Māori studies, 1999)

Land purchase methods and their effect on Maori population, 1865-1901. - Sorrenson, M. P. K. (Journal of the Polynesian Society, 1956)

Never-ending beginnings: The circularity of mana wāhine - Simmonds, Naomi (Mana Wāhine reader: A collection of writings, 1999)

Maori women: Discourses, projects and mana wahine - Smith, Linda Tuhiwai (Women and education in Aotearoa, 1992)

Old myths and new politics: Some contemporary uses of traditional history - O'Regan, Tipene (New Zealand Journal of History, 1992)

The Genesis of Maori Activism - Walker, Ranginui (Journal of the Polynesian Society, 1984)
Source: National Library of New Zealand Te Puna Matauranga o Aotearoa, licensed by the Department of Internal Affairs for re-use under the Creative Commons Attribution 3.0 New Zealand Licence.
Keywords: activism; iwi; land development; land tenure; parliament; rangatiratanga; rohe; self-determination; sovereignty; tiriti o waitangi/treaty of waitangi

Land Alienation at Waikeremoana - Wiri, Rapata (He Pukenga Korero: a journal of Māori studies, 1996)
Keywords: land alienation; land loss; land theft; mātauranga māori; social life and customs; tāngata whenua

Rangatiratanga and Sovereignty by 2040 - Kāwharu, Hugh (He Pukenga Korero: a journal of Māori studies, 1996)
Keywords: consultation; crown; hapū; iwi; mātauranga māori; social life and customs; tiriti o waitangi/treaty of waitangi; tāngata whenua; waitangi tribunal

Waitangi Day Address 1996 - Durie, Edward (He Pukenga Korero: a journal of Māori studies, 1996)
Keywords: Waitangi Day; mātauranga māori; social life and customs; tiriti o waitangi/treaty of waitangi; tāngata whenua

Tino Rangatiratanga: Māori Self Determination - Durie, Mason (He Pukenga Kōrero: a journal of Māori studies, 1995)
Keywords: kotahitanga; mātauranga māori; social life and customs; tino rangatiratanga; tāngata whenua

Hybridity in the Third Space: Rethinking Bi-cultural Politics in Aotearoa/New Zealand - Meredith, Paul (He Pukenga Korero: a journal of Māori studies, 1999)
Keywords: bicultural; government; mātauranga māori; post-colonialism; social life and customs; tāngata whenua

Self-Determination and Redistributive Justice: The New Zealand Māori - Sullivan, Ann (He Pukenga Korero: a journal of Māori studies, 1998)
Keywords: crown policy; mātauranga māori; rangatiratanga; self-determination; social life and customs; tiriti o waitangi/treaty of waitangi; tāngata whenua; welfare policies

Rethinking Claims-making as Māori Affairs Policy - Fleras, Augie; Maaka, Roger (He Pukenga Korero: a journal of Māori studies, 1998)
Keywords: crown policy; māori affairs; mātauranga māori; policy; social life and customs; treaty claims; tāngata whenua

Towards a Theory of Mana Wahine - Jahnke, Huia Tomlins (He Pukenga Korero: a journal of Māori studies, 1997)
Keywords: mana wāhine; mātauranga māori; social life and customs; te ao Māori; tikanga | indigenous law; tāngata whenua

The Genesis of Direct Negotiation, the Fiscal Envelope and Their Impact on Tribal Land Claim Settlements - Walker, Ranginui (He Pukenga Korero: a journal of Māori studies, 1997)
Keywords: mātauranga māori; national party; parliament; social life and customs; treaty settlements; tāngata whenua

Māori Perspectives on Asia/New Zealand Partnerships - Hapi, Robin (He Pukenga Korero: a journal of Māori studies, 1997)
Keywords: economic aspects; fisheries; international relations; mātauranga māori; social life and customs; tāngata whenua

Representation, Governance and the Goals of Māori Self Determination - Durie, Mason (He Pukenga Korero: a journal of Māori studies, 1997)
Keywords: māori electorates; mātauranga māori; parliament; representation; social life and customs; tino rangatiratanga; tāngata whenua

Māori Representation in Parliament and Tino Rangatiratanga - Dahlberg, Tina (He Pukenga Korero: a journal of Māori studies, 1996)
Keywords: government; māori electorates; mātauranga māori; parliament; social life and customs; tino rangatiratanga; tāngata whenua

A Permanent Expedient? MMP and Māori Politics - Keenan, Danny (He Pukenga Korero: a journal of Māori studies, 1996)
Keywords: elections; government; kāwanatanga; mātauranga māori; representation; social life and customs; tāngata whenua

The Intellectual Rangatahi: A Privilege or a Sellout? - Taumaunu, Kura (Te Pua, 1992)
Keywords: activism; mana wāhine; periodicals; sexism; wāhine māori

The Conscientisation and Politicisation of Maori Women - Nepe, Tuki (Te Pua, 1992)
Keywords: colonisation; decolonisation; discrimination; economic inequality; inequality; intersectionality; mana wāhine; periodicals; sexism; wāhine māori

On the Maori Seats - Kaa, Kuki (1964)

The Role of Maori women in Treaty Negotiations and Settlements - Rangiheuea, Tania (1995)
Keywords: crown; māori decision making; tino rangatiratanga; treaty settlements; wāhine māori

New Zealand Immigration and the Political Economy - Walker, Ranginui J (The Social Contract, 1993)
Keywords: economics; immigration policy; policy making

Mana Maori Motuhake: Maori Self-Determination - Levine, Hal; Henare, Manuka (Pacific Viewpoint, 1994)
Keywords: elections; he whakaputanga; land loss; mana motuhake; tino rangatiratanga; tiriti o waitangi/treaty of waitangi; urbanisation; waitangi tribunal

The practice of tribalism in postcolonial New Zealand - Sullivan, Ann (Cultural Studies, 1995)
Keywords: post-colonialism; tikanga | indigenous law; tino rangatiratanga; tiriti o waitangi/treaty of waitangi; urbanisation

Screaming from the shadows: Māori views on the treaty claims settlement process - McDowell, Tiopira (Te Pouhere Kōrero Journal, 1999)
Keywords: history; periodicals; treaty claims; waitangi tribunal

The 1996 General Election and the Labour vote in the Māori electorates - O'Sullivan, Dominic (He pūkenga kōrero : a journal of Māori studies, 1999)
Explores the background to Māori representation in Parliament before tracing the development of Labour's acquisition of the Māori vote up until 1...
Keywords: kāwanatanga; labour party; mmp electoral system; māori electorates; māori seats; parliament; ratana

Knowing their place: the political socialisation of Maori women in New Zealand through schooling policy and practice, 1867-1969 - Jenkins, Kuni; Matthews, Kay Morris (Women's History Review, 1998)
Nineteenth-century British missionaries and the colonial government in New Zealand adopted a policy of assimilation of Maori into Pakeha (European) culture through actively discouraging Maori language, belief systems and culture. Central to the goal of assimilation was a Native School policy which in particular, emphasised the ‘Europeanising’ of young Maori. Church-run schools for Maori, which were subsidised by the state, aimed to return young Maori to their homes to model a Christian Pakeha lifestyle. This article argues that it was Maori girls, rather than Maori boys who were viewed as critical agents of change in the transformation of Maori society and that the colonial curriculum they were taught led to a political socialisation of generations of Maori women.
Keywords: assimilation; christianity; education; identity; te reo māori; wāhine māori

Ka Pu Te Ruha, Ka Hao Te Rangatahi - Kukutai, Tahu; Webber, Melinda (1995)
Keywords: colonisation; demographic aspects; identity